Cattle hypocuprosis in Argentina associated with periodically flooded soils - Ramírez, Carlos Eduardo (1998)
Although it has been known for a long time that hypocuprosis affects cattle in the province of Buenos Aires (Argentine), mostly during the spring, there has been no attempt to estimate the occurrence of this deficiency. A survey involving more than 200 farms was carried out in five districts of the Salado river basin, where hypocuprosis is endemic. A total of 4750 plasma samples were obtained during 1993 to 1996, and the Cu content was analyzed by atomic absorption spectro- photometry. Fifty-six per cent of cattle population in the five districts was hypocupremic (plasma Cu,60 mg dl21), while 14% was severely hypocupremic (,29 mg dl21). The highest incidence was during 1994, when 71% of cattle was hypocupremic and 26% was severely hypocupremic. During the spring a maximum of 37% of cattle was severely hypocupremic, which agrees with previous findings. The causes of hypocuprosis have been defined for the area, as low forage Cu with high S and Fe mainly during the autumn. A positive association between the occurrence of hypocuprosis and excesses of rainfall was found, that explain the seasonal pattern of hypocuprosis and the influence of floodings on hypocuprosis.